Conditions of youth transition: individual and municipal factors related to the NEET rate in Finland - Ahlroth, Essi; Laaninen, Markus; Niemelä, Mikkko (Taylor & Francis, 2025)
The increasing number of youths who are not employed or studying – that is, youth not in education, employment, or training (NEET) – has been one of the most pressing issues for welfare societies in recent decades. We examined how individual characteristics and municipal conditions are associated with the NEET rate in Finnish municipalities. Utilizing full-population register data and 2-level random intercept models, we investigated youth aged 19–29 in 2017. We found that men, youth with lower levels of education, and migrant youth had a higher NEET rate, as anticipated. Contrary to expectations, however, the NEET rate was highest among older individuals. We found that benefiting from the availability of entry level jobs is tied to individual characteristics, whereas a better labor demand benefits all. The availability of public services is not associated with the NEET rate, suggesting that more in-depth exploration of public services is needed. While municipal differences in the NEET rate are explained mostly by individual factors as well as labor market factors, we noted geographic patterns in the NEET rate distribution, which implies the presence of unobserved factors. Our results provide support for labor demand policies and underline the importance of local actors.